PKK Strategies in Empowering Rural Women: A Study of Non-Formal Education in Banyumas - Amalia Ramadhani (Universitas Negeri Semarang, 2026)
This study explains the strategy to increase women’s empowerment through non-formal education in Kabupaten Banyumas, Indonesia. The research focuses on the role of women’s community organizations, particularly Pemberdayaan Kesejahteraan Keluarga (PKK) in knowledge, economic competencies, leadership capacities, and social participation at the village. This research use a qualitative method. The location of this research is in Kemutug North and Melung villages. The results indicate that empowerment strategies include: first, entrepreneurial skills training, such as ecoprint production, food processing, handicrafts, and homestay management. Second, family health counseling, digital literacy, and education. Third, building community-based economic networks. There are challenges, namely time constraints, domestic responsibilities, limited capital, lack of program sustainability, and limited market access. Women’s communities have solution for these challenges through time management, continuous practice, internal collaboration, the utilization of digital tools, and build engagement with families. In conclusion, village women’s communities have a significant role in empowerment and gender equality through non-formal education. PKK broadens women’s access to knowledge, practical skills, strengthens their participation in community leadership and making decisions. This study recommends cross sectoral collaboration in sustained mentoring to ensure the long term sustainability and effectiveness of women’s empowerment programs in rural areas.